Dampak Tari Budaya Gayo Tari Saman dalam Tradisi Islam di Desa Titi Pasir Kecamatan Semadam Kabupaten Aceh Tenggara - Husaini, Alpahmi; Kamaluddin, Kamaluddin; Fitriani, Fitriani (Lembaga Yasin AlSys, 2023)
This research examines the cultural impact of the Gayo saman dance on the Islamic tradition in Titi Village. This type of research is field research (research in the field) which is a research carried out by collecting data by research at locations where there are symptoms that will be examined to find facts found in society. The results of this study are that the Saman Gayo dance choreography is not an ordinary dance work, but Saman is a dance that contains basic Islamic concepts symbolized through rhythm, movement, poetry, floor patterns, clothing, stages of performance, purpose of offerings. From the choreography produced, it can be seen that the Saman Dance is a symbol of the Gayo tribe in carrying out Islamic law in their daily lives, so that the Saman Dance is synonymous with Islam and in accordance with the customary system in Acehnese society, namely